Acquired thrombotic thrombocytopenic purpura with possible association with AstraZeneca‐Oxford COVID‐19 vaccine. Issue 3 (18th May 2021) - Al‐Ahmad, Mona; Al‐Rasheed, Mona; Shalaby, Neveen Abo Bakr
Abstract: Acquired thrombotic thrombocytopenic purpura is characterized by the microvascular aggregation of platelets and microangiopathic hemolytic anemia causing ischemia of multiple organs including the brain mainly and less likely the kidney and the heart. The disease is caused by severe reduction in the activity of ADAMTS 13 due to presence of inhibitory antibodies.